2006
DOI: 10.1002/hed.20461
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional factors and survival of patients with oral cancer

Abstract: Apart from clinical features, nutritional factors also had a significant influence on the survival of patients with oral cancer. Therefore, good nutritional status is crucial for patients with oral cancer in improving their survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 18 publications
4
76
1
1
Order By: Relevance
“…Co-existence of smoking and tobacco chewing in drinkers is highly apparent in those consuming less vegetables and fruits (Cancela et al, 2009). Better pre-operative nutritional status helps in improving the survival of OC patients (Liu et al, 2006). The situation may be further complicated by poor socio-economic conditions.…”
Section: Mortality and Survivalmentioning
confidence: 99%
“…Co-existence of smoking and tobacco chewing in drinkers is highly apparent in those consuming less vegetables and fruits (Cancela et al, 2009). Better pre-operative nutritional status helps in improving the survival of OC patients (Liu et al, 2006). The situation may be further complicated by poor socio-economic conditions.…”
Section: Mortality and Survivalmentioning
confidence: 99%
“…No signiWcant evolution in the management of oral cancer has been developed in recent years. Even though better combinations of locoregional treatment modalities have improved the quality of life after diagnosis, the relative 5-year survival rate has not changed much over the past decades [2]. Consequently, recognition of poor prognostic factors has become a focus in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…31 Liu S et al also demonstrated that pretreatment serum albumin levels are independent indicator of prognosis for patients with oral cavity cancer. 34 A prospective cohort study of 170 patients with advanced cancer, where lung (34%), liver (14%), and lower gastrointestinal tract (14%) malignancies accounted for almost two thirds of the primary cancers, enrolled into the palliative care unit of a regional hospital in Hong Kong demonstrated that serum albumin is an independent predictor of survival. 35 Furthermore, these findings have also been reproduced in carcinoma of lung cancer, pancreatic cancer, gastric cancer, colorectal cancer and breast cancer with increasing evidence that serum albumin can be a prognostic factor in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A vast majority (>70%) of more than one billion population of India lives in rural areas, which have inadequate access to trained providers and limited health services. As a result, most of the cases are diagnosed at later stages which result in low treatment outcomes and poor 5-year survival rate of approximately 37% (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). 2 Various clinical, biochemical, and histological prognostic factors have been identified in the literature, some generic to all cancers and some specific for oral cavity cancer.…”
Section: Introductionmentioning
confidence: 99%